Effectiveness and Feasibility of Pharmacist-Driven Penicillin Allergy De-Labeling Pilot Program without Skin Testing or Oral Challenges - You-Chan Song; Zachary J. Nelson; Michael A. Wankum; Krista D. Gens (MDPI AG, 2021)
Documented penicillin allergies have been associated with an increased risk of adverse outcomes. The goal of this project was to assess the effectiveness and feasibility of a pharmacist-led penicillin allergy "de-labeling" process that does not involve labor-intensive skin testing or direct oral challenges. Adult patients with penicillin allergies were identified and interviewed by an infectious diseases pharmacy resident during a 3-month pilot period. Using an evidence-based standardized checklist, the pharmacist determined if an allergy qualified for de-labeling. In total, 66 patients were interviewed during the pilot period. The average time spent was 5.2 min per patient interviewed. Twelve patients (18%) met the criteria for de-labeling and consented to the removal of the allergy. Four patients (6%) met the criteria but declined removal of the allergy. In brief, 58.3% of patients (7/12) who were de-labeled and 50% of patients (2/4) who declined de-labeling but had their allergy updated to reflect intolerance were subsequently prescribed beta-lactam antibiotics and all (9/9, 100%) were able to tolerate these agents. A pharmacist-led penicillin allergy de-labeling process utilizing a standardized checklist is an effective and feasible method for removing penicillin allergies in patients without a true allergy.